Refleksi Unit Usaha Simpan Pinjam dan Transformasi Digital Bumdes Karya Sejahtera Desa Geneng, Jepon - Rosalia, Amelia Choya Tia; Joko Priyanto (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
Geneng Village, located in Jepon Sub-district, Blora Regency, has a population of 2,544 residents spread across four hamlets. In 2019, the village established the Village-Owned Enterprise (BUMDes) "Karya Sejahtera" with its main business unit focused on savings and loans, initiated with a starting capital of IDR 45 million sourced from the Village Fund. This service offers collateral-based loans with a 2% interest rate, serving as an administrative fee. The number of borrowers has fluctuated over the years, starting with 45 people in 2019, dropping significantly to 17 in 2020, then gradually recovering to 28 in 2021, 26 in 2022, 27 in 2023, and 29 in 2024. Despite the temporary decline, community interest has remained relatively stable over the past five years. Recognizing the stagnation in growth, at the beginning of 2025 BUMDes initiated a transformation through restructuring its management and digitizing its record-keeping system to replace the previous manual method. The 2025–2026 development plan focuses on supporting local micro, small, and medium enterprises (MSMEs) through financial management and digital marketing training. This initiative aims to increase community participation while simultaneously stimulating the village economy. Through these innovations, BUMDes reaffirms its commitment to strengthening its role as a driver of prosperity for the people of Geneng.